The changing meanings of the welfare state : histories of a key concept in the Nordic countries - Edling, Nils (Berghahn Books, 2019)
In discussions of economics, governance, and society in the Nordic countries, "the welfare state" is a well-worn analytical concept. However, there has been much less scholarly energy devoted to historicizing this idea beyond its postwar emergence. In this volume, specialists from Denmark, Finland, Sweden, Norway, and Iceland chronicle the historical trajectory of "the welfare state," tracing the variable ways in which it has been interpreted, valued, and challenged over time. Each case study generates valuable historical insights into not only the history of Northern Europe, but also the welfare state itself as both a phenomenon and a concept.